O Estágio Profissional Motivação e Educação, um Estímulo para a Superação - Emanuel Jesus Mendes Brito (2021)
The Professional Internship is part of the study plan for the 2nd year of the Master in Physical Education Teaching in Basic and Secondary Education, from the Faculty of Sport of the University of Porto. This experience aims to prepare the trainee student for a real experience with regard to the teaching of Physical Education in schools, being therefore accompanied by professionals in the field (faculty advisor at the Faculty and cooperating professor at the school). During this experience, measures and theories learned in the undergraduate program were applied, as well as the first year of the Master's degree. This document also aims to report all the experiences and reflections lived during the internship year, from the first impact with the students to the last speech. It also boils down to problems related to the pedagogical practice in what refers to the good motor commitment and motivation of the students. It reflects the experience of online classes and their adaptation to this distance learning model. The academic year is essentially marked by this situation, (COVID-19), which is new for all those who teach. All the adaptations that we had to undergo, from fulfilling distances, adapting exercises so that the students are away and getting means and ends to be able to motivate them to the practice of Physical Education.